A new family for 'termite gut treponemes': description of Breznakiellaceae fam. nov., Gracilinema caldarium gen. nov., comb. nov., Leadbettera azotonutricia gen. nov., comb. nov., Helmutkoenigia isoptericolens gen. nov., comb. nov., and Zuelzera stenostrepta gen. nov., comb. nov., and proposal of Rectinemataceae fam. nov. Issue 5 (31st May 2022) - Brune, Andreas; Song, Yulin; Oren, Aharon; Paster, Bruce J.
Abstract : The intestinal tracts of termites are abundantly colonized by a diverse assemblage of spirochetes. Most of them belong to 'termite cluster I', a monophyletic group within the radiation of the genus Treponema that occurs exclusively in termite guts. Phylogenomic analysis revealed that members of the genus Treponema are extremely diverse and represent two separate, family-level lineages: the Treponemataceae sensu stricto, which comprise the majority of the validly described Treponema species, and a second lineage that comprises the remaining members of the genus Treponema, including all members of 'termite cluster I' from termites and the recently isolated Breznakiella homolactica from cockroaches. Here, we present the formal description of Breznakiellaceae fam. nov. and of the new genera required to accommodate the misplaced Treponema species in the new family as new combinations ( Leadbettera azotonutricia, Gracilinema caldarium, Helmutkoenigia isoptericolens and Zuelzera stenostrepta) . To avoid paraphyly of Treponemataceae, we propose Rectinemataceae fam. nov. to include the genus Rectinema .